(untitled) (Ustozlar uchun, 2025)
Toponyms represent an important linguistic and cultural component of language documentation. In Uzbek lexicography, the treatment and representation of toponyms in dictionaries reflect both linguistic realities and cultural identities. This study examines the methodologies and principles underlying the expression of toponyms in Uzbek dictionaries, analyzing a selection of authoritative lexicographic sources. The findings indicate variations in the inclusion, classification, and phonological representation of toponyms, highlighting challenges and recommending improvements in future dictionary editions.